PERLINDUNGAN HUKUM TERHADAP MONETISASI KARYA SENI MUSIK UNTUK KONTEN VIDEO YANG DIUNGGAH KE YOUTUBE DITINJAU UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Martin Eka Dwi Chandra; Nahrowi Nahrowi; Mara Sutan Rambe (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
In today's rapid technological developments, many people are involved in the world of electronic entertainment and one of them is being a content creator on Youtube. However, in practice there are still many people who use other people's copyrighted works for their video content without having the approval or license of the related parties. This research focuses on circulating literature sources and the result is that every activity that uses the copyrighted work of others must have permission from the creator and/or copyright holder in accordance with Law Number 28 of 2014, besides that Youtube itself has regulated the Copyright Matching Tool. or plagiarism checking tools owned by Youtube.